Base Mediated 7-exo-dig Intramolecular Cyclization of Betti-propargyl Precursors: An Efficient Approach to 1,4-oxazepine Derivatives - Yazzaf, Rozita; Asadi, Mina; Mahdavi, Mohammad (Current Organic Synthesis, 2025)
Introduction1,4-oxazepine is a significant structural motif found in several bioactive molecules used in the treatment of diseases such as psychotic disorders.MethodsTherefore, developing novel methodologies for its preparation is of great interest to medicinal chemists.ResultsThese seven-membered heterocycles are generated through the intramolecular cyclization of Betti bases, which are propargylated using propargyl bromide as the source of the triple bond in the presence of a base.ConclusionThis efficient and straightforward protocol proceeds under mild, metal-free conditions and has been shown to be applicable to a broad range of aldehydes and 2-aminopyridines.
Keywords: propargyl bromide